Relationships of the trade unions with the media: The Lithuanian case - Asta Krašenkienė; Lina Kazokienė; Dalia Susnienė (Administrative Sciences, 2014)
The various practices of different countries show that, in order to achieve trade unions' goals, working relationships with the media are very important, especially in terms of influencing public (stakeholder) opinion, as well as instilling confidence in trade unions. This paper presents some examples and empirical research results that prove the significance of such relationships. The situation in Lithuania is analyzed based on qualitative research results. The results reveal that Lithuanian trade unions do not have effective tools at their disposal for the promotion of their activity. Moreover, their notion of their relationships with the media is limited to a narrow understanding such as "the article or broadcast in media". Due to this and other reasons, the promotion of employers' concessions is weak. Different situations can be noticed by analyzing the independent trade unions which use other practices and systems.
Keywords: 350; trade union; media; relationships; stakeholders